Daily Measurements from Cardiac Implantable Electronic Devices to Assess Health Status - Eva Roseboom; Fenna Daniëls; Michiel Rienstra; Alexander H. Maass (Diagnostics)
Cardiac implantable electronic devices (CIEDs) such as pacemakers and implantable cardioverter-defibrillators (ICDs) are increasingly used in the aging population. Modern CIEDs perform daily measurements, mainly aimed at discovering early signs of battery depletion or electrode dysfunction. Changes in thresholds, intracardiac signals, and pacing impedances can be caused by exacerbation of existing conditions or novel clinical problems. Pacing percentages and heart rate histograms can be used to optimize pacemaker programming, but can also be a measure of altered cardiac health status. Several measurements, such as thoracic impedance and patient activity, have been added to inform practitioners about worsening heart failure. In addition, remote monitoring of daily CIED measurements may accommodate for the prevention of the deterioration of clinical conditions. In this review, we discuss the evidence base of CIED algorithms and suggest how to use standard daily measurements to monitor the cardiac and extracardiac health status of patients with CIEDs.